Keats's Letters and Lamia - Yang, Chunhong (Advances in Social Sciences Research Journal, 2017)
Keats’s Lamia is known for its ambiguity, but critics fail to trace its cause. In Keats’s Letters, he reveals his split attitudes to women, similar to his ambiguous feelings towards Lamia. From his Letters, his creation of an ambivalent beauty is understood.